2016
DOI: 10.3748/wjg.v22.i31.7006
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic aspects of adult patients with nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a major cause of chronic liver disease and it encompasses a spectrum from simple steatosis to steatohepatitis, fibrosis, or cirrhosis. The mechanisms involved in the occurrence of NAFLD and its progression are probably due to a metabolic profile expressed within the context of a genetic predisposition and is associated with a higher energy intake. The metabolic syndrome (MS) is a cluster of metabolic alterations associated with an increased risk for the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
124
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(128 citation statements)
references
References 93 publications
1
124
0
3
Order By: Relevance
“…[13] NAFLD has frequently been associated with many metabolic abnormalities, such as insulin resistance, obesity, type 2 diabetes mellitus, and hyperlipidemia, which are the main features of MetS. [14] It has been reported that approximately 90% of the NAFLD patients present more than 1 component of MetS, and about 33% of the patients meet the criteria of MetS. [15] Recent studies have demonstrated a close relationship between serum UA and NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…[13] NAFLD has frequently been associated with many metabolic abnormalities, such as insulin resistance, obesity, type 2 diabetes mellitus, and hyperlipidemia, which are the main features of MetS. [14] It has been reported that approximately 90% of the NAFLD patients present more than 1 component of MetS, and about 33% of the patients meet the criteria of MetS. [15] Recent studies have demonstrated a close relationship between serum UA and NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies considered NAFLD as a hepatic border of metabolic syndrome (Abenavoli et al 2016). It can progress to liver cirrhosis and end-stage liver disease, and is one of the important causes of hidden-source cirrhosis (Chalasani et al 2012).…”
Section: Dintroductionmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) is a liver entity characterized by elevated serum aminotransferase levels and accumulation of fat in liver accompanied occasionally by inflammation and necrosis resembling alcoholic hepatitis in the absence of heavy alcohol consumption [1][2]. This is the most common chronic liver disease in Western populations and it has been related with metabolic syndrome, adipokines, and insulin resistance [3].…”
Section: Introductionmentioning
confidence: 99%